CARDIOVASCULAR AND RENAL OUTCOME OF LIVING KIDNEY DONORS ON A LONG TERM. - Kumar, Prashant; Kumar, Akhilesh; Raj, Rahul (Student’s Journal of Health Research Africa, 2023)
Background: Removal of one or more kidneys may result in reduced renal parenchyma and GFR. Hence it is essential to gain proper knowledge of clinical symptoms before donating the kidney. The main aim of this study is to analyze the long-term renal and cardiovascular outcomes in living kidney donors. Materials and methods: It was a retrospective, observational study in a single center. A total of 62 living kidney donors from Darbhanga Medical College and Hospital in Laheriasarai, Bihar, from September 2022 to August 2023 were selected for this study. Their initial data (visit 0) from the time of the study to their last nephrological data (visit 1) were obtained and compared. Results: There was a huge drop in glomerular filtration rate which was about 28mL/min in a phase of 82±60 months. One donor underwent chronic kidney failure according to his last nephrological checkup (visit 1). There was no association between the age group and reduced glomerular filtration rate. Conclusion: The decrease in glomerular filtration rate as a consequence of kidney donation may cause an adverse reaction in renal and cardiovascular outcomes. Recommendation: The age of the donor does not signify the occurring consequences so older and healthy donor individuals are also recommended.